Intelligence of Low Dimensional Topology 2006: Hiroshima, Japan, 22-26 July 2006 - Carter, J. Scott (Series on knots and everything, 2007)
This volume gathers the contributions from the international conference "Intelligence of Low Dimensional Topology 2006," which took place in Hiroshima in 2006. The aim of this volume is to promote research in low dimensional topology with the focus on knot theory and related topics. The papers include comprehensive reviews and some latest results